Graduate Trainees' Social Justice Supports, Beliefs, Interest, and Commitment. (August 2015) - Inman, Arpana G.; Luu, Linh P.; Pendse, Asmita C.; Caskie, Grace I. L.
The present study examined the direct and indirect relationships between belief in a just world, belief in an unjust world, perceived social supports, and training supports, and social justice self-efficacy beliefs, interest, and commitment among 274 graduate counselor trainees. Structural equation modeling revealed that social justice self-efficacy had direct and indirect effects on social justice commitment by bolstering social justice interest. Furthermore, the more participants believed that the world was a just place, the less interest and commitment they expressed for social justice advocacy. Moreover, the more social support, training supports, social justice self-efficacy, and interest participants reported, the higher their commitment to doing social justice work. Finally, training supports only had a direct link to social justice commitment. Implications for theory, training programs, and research are addressed.